The value of quantitative environmental DNA analyses for the management of invasive and endangered native fish. (13th June 2021) - Rojahn, Jack; Pearce, Luke; Gleeson, Dianne M.; Duncan, Richard P.; Gilligan, Dean M.; Bylemans, Jonas
Abstract: Environmental DNA (eDNA) monitoring is a useful tool for species detection but its use in addressing management questions remains scarce. One factor limiting the use of eDNA as a routine monitoring tool is uncertainty around the potential of eDNA data to estimate species abundance. While several confounding factors limit the ability of eDNA data to estimate absolute abundances at large spatial and temporal scales, eDNA data have the potential to estimate relative species abundances patterns at smaller scales, and this information can assist management. Environmental DNA and conventional monitoring surveys were conducted in the Abercrombie River catchment (Australia) where an incursion of the invasive redfin perch ( Perca fluviatulis) threatens the survival of a population of endangered Macquarie perch ( Macquaria australasica) . Species‐specific assays were used to quantify eDNA concentrations from water samples and estimate the relative abundance of both species. Electrofishing and fyke netting surveys were used to validate key observations from the eDNA survey. Environmental DNA of both species was detected at all sites except one, where redfin perch DNA was not detected. Between species comparisons of eDNA concentrations revealed a clear negative relationship between the eDNA concentrations of both species, consistent with other evidence of redfin perch having a negative impact on Macquarie perch populations. Between site comparisons of redfin perch eDNA concentrations showed evidence of a novel incursion of the species in the upper reaches of the Abercrombie River and conventional monitoring in the following year confirmed the pattern of increased redfin perch abundances from downstream to upstream sites. Relative comparisons of eDNA concentrations of aquatic species can be used to assess species interactions and reveal unexpected species abundance patterns (e.g. allowing inferences of novel incursions of invasive species). This information is critical to evaluate current, and design future, management strategies. Consequently, while deriving absolute species abundances from quantitative eDNA data may remain challenging, the use of quantitative eDNA surveys can provide relative abundance patterns valuable to the conservation and management of invasive and endangered species. The quantitative nature of eDNA survey data has been debated extensively in the current literature because of potential confounding influences. Current study results show that these confounding influences may be less problematic at small spatial scales and quantitative eDNA data can be effective to monitor relative species abundances patterns.